John Laband, The Assassination of King Shaka (Historia, 2021)
As noted in the Acknowledgements to Fieldwork of Empire, 1840–1900: Intercultural Dynamics in the Production of British Expeditionary Literature, this work has been long in the making. The original ideas behind it first emerged in the early 2000s. This passage of time has allowed for the ideas on offer to be explored in‐depth and detail; to brew and mature into a substantive, convincing piece of scholarship. The publication is a valuable contribution to the field of Victorian colonial literature, though its impact will resonate more widely. The work will appeal to scholars from a broad spectrum of disciplines working on the nineteenth‐century history of British colonialism in Africa. In particular, the book delivers a path‐breaking contribution to the history of the production of “knowledge” of Africa via Victorian expeditionary literature.
Keywords: Laband; King Shaka; South Africa; Empire